PENGEMBANGAN HANDOUT DIGITAL ANYFLIP PADA MATERI MENGANALISIS LIMBAH BUSANA SUB TEMA OUTER ORIGAMI RABBIT ZERO WASTE - Nabilah, Nevi; Wahyuningsih, Urip (Universitas Negeri Surabaya, 2021)
In the era of globalization and the industrial revolution 4.0, it demands innovation and optimal use of technology in learning. This research is motivated by the results of the development of handout digital on the material of analyzing clothing waste in the sub-theme of the outer origami rabbit zero waste. The stages of assessment and development of this handout digital refer to the ADDIE development model which analysis, design, development, implementation, and evaluation. The purpose of writing this article are: 1) Developing handout digital using Anyflip on the subject matter of analyzing clothing waste with the sub-theme of outer origami rabbit zero waste, 2) Knowing the feasibility of the validator for handout digital using Anyflip on the subject matter of analyzing clothing waste with the sub-theme of outer origami rabbit zero waste. The research instrument used in the form of a validation sheet and for data analysis using descriptive analysis with a percentage. The conclusions of the results of this study are 1) The development of handout digital using Anyflip on the subject matter of analyzing clothing waste with the sub-theme of the outer origami rabbit zero waste can be used as a learning medium at SMK Tata Busana, 2) The results of the feasibility validation assessment of handout digital using Anyflip on the subject matter of analyzing clothing waste with the sub-theme of outer origami rabbit zero waste of language experts 81,8%, media experts 81,6%, and theory experts 94.5%. With the results of this study, handout digital are stated to be very good to used as an efficient and easy to use learning medium. Pada era globalisasi serta revolusi industri 4.0 menuntut inovasi dan pemanfaatan teknologi dalam pembelajaran secara optimal. Penelitian ini dilatarbelakangi dari hasil pengembangan handout digital pada materi menganalisis limbah busana sub tema outer origami rabbit zero waste. Tahapan penilaian dan pengembangan handout digital menggunakan model pengembangan ADDIE dengan tahap analysis, design, development, implementation, dan evaluation. Tujuan penulisan artikel ini adalah: 1) Melakukan pengembangan handout digital menggunakan Anyflip pada materi pokok mengalisis limbah busana dengan sub tema outer origami rabbit zero waste, 2) Mengetahui kelayakan dari validator terhadap handout digital menggunakan Anyflip pada materi pokok mengalisis limbah busana dengan sub tema outer origami rabbit zero waste. Instrumen penelitian yang digunakan berupa lembar validasi dan untuk analisis data menggunakan analisis deskriptif dengan persentase. Kesimpulan hasil penelitian ini adalah 1) Pengembangan Handout digital menggunakan Anyflip pada materi pokok mengalisis limbah busana dengan sub tema outer origami rabbit zero waste dapat digunakan sebagai media pembelajaran pada SMK Tata Busana, 2) Hasil penilaian validasi kelayakan handout digital menggunakan Anyflip pada materi pokok mengalisis limbah busana dengan sub tema outer origami rabbit zero waste yaitu ahli bahasa 81,8 %, ahli media 81,6%, dan ahli materi 94,5%. Dengan hasil penelitian tersebut handout digital dinyatakan sangat baik digunakan sebagai media pembelajaran yang efisien dan mudah digunakan.